Geometric Thinking Levels in Learning Quadrilaterals: A Van Hiele-Based Case Study in a Papuan Junior High School - Tandililing, Pitriana; Sirampun, Elsi; Kho, Ronaldo; Ruamba, Marthinus Yohanes (Edumatica : Jurnal Pendidikan Matematika, 2025)
This study investigated the geometric thinking levels of eighth-grade students in a Papuan junior high school, using the van Hiele theoretical framework, with a focus on their understanding of quadrilaterals. The research addressed common misconceptions and limited conceptual understanding among students by exploring how they classified, identified, and described the properties of quadrilaterals. A qualitative descriptive design was employed, involving 25 students selected through purposive sampling. Data were collected using structured interviews, drawing tasks, and classification activities. The primary instrument included three tasks: drawing various quadrilaterals, identifying and defining their properties, and classifying them based on shared attributes. The results showed that 50% of students operated at van Hiele Level 0 (Visualization), 36% were transitioning between Level 0 and Level 1 (Analysis), and only 14% reached Level 1. Students frequently relied on visual appearance rather than formal geometric attributes, leading to persistent misconceptions about hierarchical relationships among shapes. No students demonstrated reasoning beyond Level 1. The findings emphasized the need for instructional approaches that integrate cultural context, use dynamic visual tools, and scaffold learning to support higher-order geometric reasoning. Further research is recommended to develop culturally responsive models and extend the study across different educational contexts.